2018
DOI: 10.1017/dsj.2018.10
|View full text |Cite
|
Sign up to set email alerts
|

Design of urban electric bus systems

Abstract: Many public transport authorities have a great interest in introducing zero-emission electric buses. However, the transformation process from diesel to electric bus systems opens up a vast design space which seems prohibitive for a systematic decision making process. We present a holistic design methodology to identify the 'most suitable system solution' under given strategic and operational requirements. The relevant vehicle technologies and charging systems are analysed and structured using a morphological m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 104 publications
(66 citation statements)
references
References 26 publications
0
47
0
4
Order By: Relevance
“…In this section, we will give an overview to battery and charging systems and discuss the technical parameters most important for electric bus system design. For a discussion of other relevant components like body, drivetrain and auxiliaries and their influence on electric bus system design we refer to Göhlich et al (2018). .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we will give an overview to battery and charging systems and discuss the technical parameters most important for electric bus system design. For a discussion of other relevant components like body, drivetrain and auxiliaries and their influence on electric bus system design we refer to Göhlich et al (2018). .…”
Section: Methodsmentioning
confidence: 99%
“…Despite recent advances in material and manufacturing processes of Li-ion batteries, the battery persists to be the limiting factor in terms of drive range and lifespan of the vehicle. A recent work, Göhlich et al (2018), identified three most competitive Li-ion battery chemistries and corresponding charging strategies, lithium iron phosphate (LFP), lithium titanium oxide (LTO) and lithium nickel manganese cobalt oxide (NMC) for E-bus systems and performed a total cost of ownership (TCO) analysis. While the work provides a holistic and thorough cost analysis, rather simplistic battery aging models have been used and therefore, their lifespans have been conservatively estimated.…”
Section: Iced19mentioning
confidence: 99%
See 2 more Smart Citations
“…The rollout of mobility solutions is accompanied by substantial challenges in the transport and energy sector. This includes, for example, the reduction of the total cost of ownership, the provision of sufficient charging infrastructures, the agreement of standards, and the formulation of regulatory requirements [1,2]. For charging processes and the provision of active energy management, a variety of limiting factors has to be taken into account [3], e.g., distance traveled, road topology, driving behavior, prevailing traffic conditions, and ambient temperature.…”
Section: Introductionmentioning
confidence: 99%